PICTURESQUE POLAROIDS: Cyprien Gaillard's modern ruin landscapes. (4th May 2019) - Gerke, Stefanie
Abstract : This paper analyses the Polaroid series Geographical Analogies (2006–2010) by French artist Cyprien Gaillard, one of many recent artworks dealing with the failure of modern architectural utopias. His representations of derelict, decaying locations evoke the tradition of picturesque ruin imagery and the article asks in what way artworks like Gaillard's update formerly relevant aesthetic categories such as the picturesque. By presenting the Polaroids in vitrines, Gaillard challenges common ideas of what kind of architecture is worthy of portrayal, protection and even monumentalising.Geographical Analogies not only reacquaints us with the picturesque, it also raises questions of moral consequence regarding the appreciation for decay.